Socio-economic condition of fish farmers of Jhikargachha upazila in Jessore district, Bangladesh - Asif, Abdulla Al; Habib, Md Ahsan Bin (Asian Journal of Medical and Biological Research, 2018)
The present study was conducted to assess the livelihood status of fish farmers and socioeconomic condition in the Jhikargachha upazila, Jessore, Bangladesh. Data were collected from 50 fish farmers for a period of six months from June 2016 to November 2016. The study indicated that 38% of the farmers were in age structure of 50-60 years, 44 farmers (88%) were Muslims and others Hindu (12%). About 82% farmers had a primary occupation of agriculture and others were involved in business (8%), service (4%) and politics (4%). It was found that, 66% farmers had joint family and others lived in separated family (34%). Majority (44 farmers) respondents had concrete house and rest of (6 farmers) had semi-concrete house. Almost (44%) farmers used concrete toilet and rest of farmers used semi-concrete (56%). All the respondents used to drink tube well water for drinking and other household works. Out of 50 fish farmers, 4% had no education (illiterate), 36% had primary education, 42% secondary level (Up to X), 10% S.S.C., 4% H.S.C. and 4% bachelor level of education. In the study area, 32% of the farmers had ponds of 34-66 dec, 28% had pond of 15-33 dec, 14% had ponds of up to 100 dec, 22% had ponds of 101-330 dec and 4% had ponds of 330-above dec. It was found that, 62% farmers had training on fish farming and rest 38% farmers had no training on fish farming. Among 50 farmers 64% farmers were found used to invest their own credit and rest 36% farmers took loan from bank, NGO, money lender and broker agency. Most of the farmers were interested to stock rui, catla and mrigal and other species. In the study area, cow dung was used by 50 (100%) of farmers, 47 farmers used urea, 40 farmers used TSP and 34 farmers used MoP. It was found that, 40% farmers produced fish between 1001 kg – 2000 kg/year and 17 (34%) farmers produced 3001 kg-above/year. The highest income was 3,30,75,000Tk/Year and the lowest income from a pond was 20000 Tk/Year. In the study area, every farmer had at least one mobile phone. Almost 96% farmers were used to go MBBS doctor and only 4% to homeopathic treatment. Asian J. Med. Biol. Res. December 2017, 3(4): 462-475